THE MARINE HEAVY FUEL IGNITION AND COMBUSTION BY PLASMA - MOROIANU CORNELIU (Fiabilitate şi Durabilitate)
The continuous damage of the used fuel quality, of its dispersion due to the increasing viscosity, make necessary the volume expansion and the rise of the e electric spark power used at ignition. A similar situation appears to the transition of the generator operation from the marine Diesel heavy fuel to the residues of water-fuel mixture. So, it feels like using an ignition system with high specific energy and power able to perform the starting and burning of the fuels mentioned above. Such a system is that which uses a low temperature plasma jet. Its use involves obtaining a high temperature area round about the jet, with a high discharge power, extending the possibility of obtaining a constant burning of different concentration (density) mixtures. Besides the action of the temperature of the air-fuel mixture, the plasma jet raises the rate of oxidation reaction as a result of appearance of lot number of active centers such as loaded molecules, atoms, ions, free radicals.